Analisis Implementasi Pembuatan Akta Tanah/Sertipikat Tanah di Badan Pertanahan Nasional Republik Indonesia Melalui Kelompok Masyarakat (POKMAS) Kantor Pertanahan Kabupaten Lampung Barat (Studi di Desa Kuta Besi Kecamatan Batu Brak Kabupaten Lampung Barat) - Lintje Anna Marpaung; Anggalana Anggalana; Eky Sepriza (Wajah Hukum, 2021)
A land certificate is important in a rule of law because it is the strongest proof of ownership owned by a person if the status of the land is to be recognized by the law, without a certificate it can be ascertained that the person who claims the land can be canceled. In addition, land certificates can also be sold or transferred to other people or inherited to their children. In the Making of Land Deeds / Certificates in Kuta Besi Village, Batu Brak District, West Lampung Regency, currently many people do not have official land certificates from BPN, therefore People who are aware of the law establish a Pokmas organization that collaborates directly with the West Lampung BPN as an effort to assist the community in making land certificates that are more efficient and effective, and also the purpose of establishing a community group organization is to provide direct socialization to the community regarding community rights to land ownership, methods This research uses a normative juridical approach using legislation related to Land Registration and an empirical approach, which is carried out by looking directly at the object of research by means of observation and interviews.